Expectation formation in case of newer hotels - Nath, Prithwiraj; Devlin, James; Reid, Veronica (SAGE, 2016)
Advertisement and price cues are important sources of information that influence tourists’ service expectations, particularly in the case of newer, less-established hotels. However, it is not clear if such hotels benefit from promising more or less through their advertisements; or price high or low through their price cues. Extant research is also uncertain about the role of culture in moderating the impact of advertisement and price cues on expectations. Using an experimental setup with 218 tourists from three different countries, this study finds that a newer hotel is likely to be better off by offering more service promises through its advertising and high price cues to its prospective visitors. The results suggest that culture influences how tourists process advertising cues but has no influence on price cue influence. The study provides insights for managers on how to develop a segmentation strategy using the cultural profiles of tourists.